Skeletal muscle mitochondrial dysfunction during chronic obstructive pulmonary disease: central actor and therapeutic target. Issue 6 (8th March 2013) - Meyer, Alain; Zoll, Joffrey; Charles, Anne Laure; Charloux, Anne; de Blay, Frédéric; Diemunsch, Pierre; Sibilia, Jean; Piquard, François; Geny, Bernard
New Findings What is the topic of this review? Muscle dysfunction is a common complication and an important independent prognostic factor in chronic obstructive pulmonary disease (COPD). What advances does it highlight? In COPD patients, the vastus lateralis muscle presents with alterations that include a decrease in mitochondrial density and biogenesis, impaired mitochondrial respiration and coupling, as well as increased mitochondrial production of reactive oxygen species, possibly associated with increased mitochondrial apoptosis. These mitochondrial changes are accessible to conventional therapies, such as exercise and tobacco cessation, but potentially also to innovative management strategies, such as antioxidant treatment and supplementation with polyunsaturated fatty acids. Mitochondrial pathophysiology represents an emerging area of research in muscle dysfunction associated with COPD and has promising therapeutic implications. Muscle dysfunction is a common complication and an important prognostic factor in chronic obstructive pulmonary disease (COPD). As therapeutic strategies are still needed to treat this complication, gaining more insight into the process that leads to skeletal muscle decline in COPD appears to be an important issue. This review focuses on mitochondrial involvement in limb skeletal muscle alterations (decreased muscle mass, strength, endurance and power and increased fatigue) in COPD. Mitochondria are the main source of energy for the cells; they are involved in production of reactive oxygen species and activate an important pathway that leads to apoptosis. In COPD patients, skeletal muscles are characterized by decreased mitochondrial density and biogenesis, impaired activity and coupling of mitochondrial respiratory chain complexes, increased mitochondrial production of reactive oxygen species and, possibly, increased apoptosis. Of particular interest, a sedentary lifestyle, hypoxia, hypercapnia, tobacco smoking, corticosteroid therapy and, possibly, inflammation participate in this mitochondrial dysfunction, which is accessible to conventional therapies, such as exercise and tobacco cessation, as well as, potentially, to more innovative approaches, such as antioxidant treatment and supplementation with polyunsaturated fatty acids.